Cobalt Phthalocyanine‐Based Photo/Electrocatalysts for Hydrogen Evolution Reaction - Sheriff A. Balogun; Dina Thole; Daniel Masekela; Kwena D. Modibane (Advanced Energy & Sustainability Research)
Cobalt phthalocyanine (CoPc)‐based catalysts have garnered significant interest as efficient materials for hydrogen evolution reactions (HER) due to their abundant availability, low cost, tunable electronic structures, and unique light absorption performance. This review offers a thorough examination of the latest developments in CoPc‐based catalysts for HER. It entails a wide range of synthesis approaches, intrinsic characteristics, and catalytic mechanisms associated with these catalysts for HER. We also compare the photo/electrocatalytic performance of these catalysts using parameters like Tafel slope, exchange current density, overpotential, hydrogen yield, turnover frequency, stability, specific surface area, etc. The review shows that the commonly used electrolytes for electrocatalytic HER are KOH, LiClO4/PBS, and H2SO4, while for photocatalytic HER, triethylamine, water, and triethanolamine are frequently used. Among all the electrocatalysts understudied, poly[CoOTPc]‐KB and GO/4N‐CoPc are the best, owing to their lowest overpotentials and Tafel slopes. In terms of photocatalytic hydrogen production, CoPc/TiO2/Pt has better photocatalytic HER performance compared to its counterparts. This review also highlights the effects of incorporating CoPc with different materials on the photo/electrocatalytic HER performance. Furthermore, the review discusses the challenges and prospects, emphasizing the chances for improving and incorporating CoPc‐based catalysts as a viable option for hydrogen production in the future.